Livelihood Transformations of the Orang Rimba as Tacit Resistance in the Context of Deforestation - Adi Prasetijo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2017)
The Orang Rimba are one of the hunter-gatherer groups remaining in Sumatra. Their livelihoods are based on managing the forest in which they live. They follow the tradition of natural resource management that is based on non-wood forest products (Ø. Sandbukt, 1988). State policies that focus on economic development since the New Order regime have ultimately affected their lives. Many forest areas and the territories in which they practice nomadism are being converted into plantations, agricultural land, and residential development, which all contribute to the condition of deforestation. State policy also does not favor the Indigenous people. If we look at spatial development in Jambi over the past 25 years, the allocation of land for other uses, such as residences, estates, and physical development, has shown little regard for the indigenous people who live in the forest region. Orang Rimba have no area left in which to roam and continue their lives as traditional hunters and gatherers. Cut off from their cultural roots, they cannot any longer live in accordance with their culture and tradition. As a group, they suffer both physical and socio-cultural displacement. Orang Rimba react to this situation in different ways to transform their livelihoods into a survival mode in order to face the everyday reality of accelerated deforestation. Under these new circumstances, Orang Rimba livelihoods can be  regarded as ‘tacit resistance’ or, to use James Scott’s term, a ‘hidden transcript’ of the weapons of the weak(Scott, 1985). They use a variety of ways to make a living, both economic and sociocultural. NGOs also have a prominent role to support the Orang Rimba. NGOs assist the Orang Rimba to put themselves in a position parallel to other communities.  This paper will look at the impact of Jambi spatial policies that have been unfavorable to Indigenous People and how the Orang Rimba respond to them